Carnosic acid. (July 2015) - Birtić, Simona; Dussort, Pierre; Pierre, François-Xavier; Bily, Antoine C.; Roller, Marc
Graphical abstract: Carnosic acid is a phenolic (catecholic) diterpene, endowed with antioxidative and antimicrobial properties. It is increasingly used within food, nutritional health and cosmetics industries. Highlights: Carnosic acid (CA) is a plastidial catecholic diterpene occurring in the Lamiaceae. CA has antioxidative and antimicrobial properties. Biosynthetic pathway and oxidative transformations of CA are proposed. CA is increasingly exploited within food, nutritional health and cosmetics industries. Abstract: Carnosic acid (salvin), which possesses antioxidative and antimicrobial properties, is increasingly exploited within the food, nutritional health and cosmetics industries. Since its first extraction from a Salvia species (∼70 years ago) and its identification (∼50 years ago), numerous articles and patents (∼400) have been published on specific food and medicinal applications of Rosmarinus and Salvia plant extracts abundant in carnosic acid. In contrast, relevant biochemical, physiological or molecular studies in planta have remained rare. In this overview, recent advances in understanding of carnosic acid distribution, biosynthesis, accumulation and role in planta, and its applications are summarised. We also discuss the deficiencies in our understanding of the relevant biochemical processes, and suggest the molecular targets of carnosic acid. Finally, future perspectives and studies related to its potential roles are highlighted.